Cryptococcus gattii genotype AFLP6/VGII meningoencephalitis in an immunocompetent Filipino male in Kuwait: activation of a dormant infection. Issue 3 (June 2015) - Alfouzan, Wadha; Al-Sheridah, Saud; Alenzi, Laila; Hagen, Ferry; Meis, Jacques F.; Khan, Ziauddin
Abstract : Introduction: Cases of Cryptococcus gattii infections are being increasingly recognized in geographical regions that were traditionally regarded as non-endemic. Here, we describe a case of C. gattii meningoencephalitis in an immunocompetent Filipino male diagnosed in Kuwait. Case presentation: A 34-year-old healthy Filipino male presented with a history of progressive generalized headache, nausea and repeated episodes of vomiting. The patient had continuously lived and worked in Kuwait for three consecutive years before developing the disease. The diagnosis of meningoencephalitis was established by demonstrating capsulated budding yeast cells in cerebrospinal fluid, isolating C. gattii in culture and detecting cryptococcal polysaccharide antigen in serum and cerebrospinal fluid specimens. Molecular characterization of the isolate confirmed its identity as C. gattii, genotype AFLP6/VGII. The isolate showed reduced susceptibility to fluconazole and was treated suboptimally until flucytosine became available. Conclusions: A case of C. gattii meningoencephalitis in a healthy Filipino male, who apparently acquired the infection in his native country, is described. The infection remained dormant for several years before becoming clinically apparent. To the best of our knowledge, this is the first report of C. gattii meningitis diagnosed in Kuwait.